2005
DOI: 10.1007/bf03325849
|View full text |Cite
|
Sign up to set email alerts
|

Study of heavy metals in urban runoff

Abstract: A cross-sectional survey was conducted through Tehran city and a field study was conducted to prepare main an d accessory drainage chann els map. Three main drainage channels were identified for this research and some sampling stations were chosen. Three stations selected in south of Tehran. The reason for selecting th ese stations is that all urban surface runoff completely pass through these points and samples taken from these points are representative of all kinds of pollutants that transit from city surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 12 publications
3
8
1
Order By: Relevance
“…This is because variations in physicochemical values at different sites contribute for the variation of metal concentration. In line with our results, Igbinosa and Okoh [18] and Sekabira et al [35] reported that the concentration of metals in aquatic ecosystems are highly correlated with physico-chemical parameters as mentioned earlier by different authors. Agrochemical substances that runoff to those sites can cause variation in metal concentration.…”
Section: Metals Concentrations In Sedimentsupporting
confidence: 93%
See 1 more Smart Citation
“…This is because variations in physicochemical values at different sites contribute for the variation of metal concentration. In line with our results, Igbinosa and Okoh [18] and Sekabira et al [35] reported that the concentration of metals in aquatic ecosystems are highly correlated with physico-chemical parameters as mentioned earlier by different authors. Agrochemical substances that runoff to those sites can cause variation in metal concentration.…”
Section: Metals Concentrations In Sedimentsupporting
confidence: 93%
“…The correlation for elemental pair such as Hg/Pb, Zn/Cd and Zn/ Pb in this study was consistent with the works of Kar et al [23] and Nirmal et al [24] and metal-physico-chemical pairs such as Cr/TDS and Zn/EC were also consistent to the work of Sekabira et al [35]. Particularly, the correlation of Zn with Pb and Cd in this study was agreed with the work of Okafor and Opuene [22].…”
Section: Metal Concentration In Aquatic Macrophytesupporting
confidence: 92%
“…The WWTP is the central unit of the UWS, receiving the polluted wastewater coming from the urban area, originated from several sources as industrial sites, households/domestic (faeces and urine, food, amalgam, detergents, pipes and taps, drinking water, artist paint), (1000) and Zn (4000); limit value for As only applies in Denmark e Chromium was deleted from the regulation in 1995, and EPA is re-examining this limit business/commercial (car washes, dentists, large enterprises), hospitals (diagnostic agents, disinfectants, pharmaceuticals), pipe sediments and surface runoff from building materials (roofs and fronts), galvanized materials, traffic (brake linings, tires, asphalt wear, gasoline/oil leakages) and agricultural areas. As a significant part of the urban soil surfaces is impermeable, metals via atmospheric deposition will also be transported with storm water to WWTPs in combined sewage pipes, or directly to water recipients (Emmanuel et al 2005;Nabizadeh et al 2005;Sörme and Lagerkvist 2002;Bergbäck et al 2001;EC 2001a). Apparently, there is not a general consensus in the literature regarding the classification of these sources, as point or diffuse sources, probably because it depends on the referential that is being considered.…”
Section: Sources Of Metals Entering the Wwtpsmentioning
confidence: 98%
“…There are now enough evidences to relate urban water deterioration to non-point sources pollution (e.g. Taebi and Droste 2004;Nabizadeh et al 2005;USEPA 2005;Atasoy et al 2006). Previous studies indicated that there were significant differences in stormwater constituents for different land use categories (Mcleod et al 2006;Pitt et al 2004;Al-Jaralla and Al-Fares 2009).…”
Section: Introductionmentioning
confidence: 99%